TOLERANSI MELALUI MODEL BUDAYA PELA GANDONG Menggunakan Media Board Game untuk Mahasiswa - Tangidy, Allez Martin; Setiawan, T. Arie (Sabda: Jurnal Kajian Kebudayaan, 2016)
Indonesia which is known by its diversity of cultures, ethnics, races, and religions can create differences which could trigger massive social conflicts. Social conflict which happened in Ambon has been one example that could tear the nation apart. In post conflict period, Pela Gandong as a local wisdom is proven to maintain the relationship in Moluccas. The culture of Pela Gandong, could be a form of national unity that can be a model to the attempt to the cohesion of the Indonesian society. The Pela Gandong is a part of Moluccas culture that contains moral value such as tolerance, unity, respect, equality, and peace. It is worth to be delivered for college students, due to the fact that college students are an important element in the modern Indonesian society. College students are the agent of change for Indonesia future. To deliver Pela Gandong culture to college students, there is a need of media which is more interactive and can simulate a society life in the future. Board game is one of the media that can simulate that condition well. Descriptive method will be used to carry out this research. The result of this research is a board game which can deliver moral values and culture of Pela Gandong.